2022
DOI: 10.7600/jpfsm.11.247
|View full text |Cite
|
Sign up to set email alerts
|

Association between sport types and visuospatial working memory in athletes

Abstract: Several studies have demonstrated that athletes show superior performance in general cognitive functions compared to non-athletes. However, the effects on cognitive function might vary depending on the athlete's sport type. In athletes, the visuospatial working memory is a crucial function for immediate response to each situation and experience. However, no studies have yet examined the association between visuospatial working memory and sport types. This study aimed to investigate whether sport type influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These include the effects of gymnastic exercises (26), active games (27), skill-based exercises (28), aerobic exercises (29), selected games (30), and spark exercises (11). Previous studies have shown that due to their different cognitive requirements, different sports can create differences in the transfer of cognitive skills, including working memory function (15). Among various sports, strategic disciplines require more cognitive skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the effects of gymnastic exercises (26), active games (27), skill-based exercises (28), aerobic exercises (29), selected games (30), and spark exercises (11). Previous studies have shown that due to their different cognitive requirements, different sports can create differences in the transfer of cognitive skills, including working memory function (15). Among various sports, strategic disciplines require more cognitive skills.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, newly acquired memory is initially influenced by consolidation mechanisms and later becomes engaged in reconsolidation mechanisms (14). Furthermore, strategic athletes likely have higher cognitive demands in visualspatial working memory since they process more visualspatial information (teammates, opponents, field positions, and the ball) compared to other types of sports (15). For example, Crova et al showed that tennis exercises, compared to aerobic exercises, led to greater improvements in working memory and inhibitory response in overweight children (16).…”
Section: Introductionmentioning
confidence: 99%
“…Sports experience and cognitive ability are intertwined, and together they shape an individual's behavior and thinking patterns. Motor experience is not only a simple accumulation of body muscle movement, but also includes the individual's cognitive ability complementary to the perception of environmental changes, the execution of the action and the feedback of the result [8][9][10][11][12][13][14][15] . It has become an established fact that exercise can effectively promote cognition.…”
Section: Introductionmentioning
confidence: 99%